Experimental and Theoretical Study of Bi2O2Se Under Compression - Pereira, A. L. J.; Santamaria-Perez, D.; Ruiz-Fuertes, J.; Manjon, F. J.; Cuenca-Gotor, V. P.; Vilaplana, R.; Gomis, O.; Popescu, C.; Munoz, A.; Rodriguez-Hernandez, P.; Segura, A.; Gracia, L.; et al. (American Chemical Society, 2018)
We report a joint experimental and theoretical study of the structural, vibrational, elastic, optical, and electronic properties of the layered high-mobility semiconductor Bi2O2Se at high pressure. A good agreement between experiments and ab initio calculations is observed for the equation of state, the pressure coefficients of the Raman-active modes and the bandgap of the material. In particular, a detailed description of the vibrational properties is provided. Unlike other Sillen-type compounds which undergo a tetragonal to collapsed tetragonal pressure-induced phase transition at relatively low pressures, Bi2O2Se shows a remarkable structural stability up to 30 GPa; however, our results indicate that this compound exhibits considerable electronic changes around 4 GPa, likely related to the progressive shortening and hardening of the long and weak Bi-Se bonds linking the Bi2O2 and Se atomic layers. Variations of the structural, vibrational, and electronic properties induced by these electronic changes are discussed.
Experimentální a teoretické studium Bi2O2Se pod tlakem
Keywords: bilbao-crystallographic-server; x-ray-diffraction; single dirac cone; crystal-structure; high-pressure; topological-insulator; thermoelectric properties; lattice-vibrations; phase-transitions; high-mobility